Ancient Greek "Myth of the Argonauts" in the Context of the Balkan Ethnogenesis - Поліщук (Шадчина) А. С. (Видавничо-поліграфічний центр "Київський університет", 2013)
The article is devoted to the interpretation of the "argonavtic myth" elements, in particular, family relations between the Corinthian and Kolhs Dynasties in the period of Bronze Age, as well as to the analysis of accompanying mythological symbols and lexics. The purpose of the work was to summarize the existing theories regarding Indoeuropean-Caucasian linguo-cultural parallels, and include in the mythology comparative studies ritual functions of the "Golden Fleece". Parallel perception of solar and zoomorphic cult symbols (ram, bull or their skins) as a sign of divine kingship, attested in Hittite rituals and marked in the Greek and Etrusco-Roman mythology, is probably originated in Western Anatolian area. To confirm the hypothesis of the Balkan-Anatolian-Caucasian contacts the doublet proper names with roots: Kaukas-, Ias-, Arg-, Aia-, – were compared on the background of known Caucasian borrowing for designation 'fleece' in ancient Greek.

Стаття присвячена інтерпретації елементів "аргонавтичного міфу", зокрема, генеалогічним зв'язкам коринфської та колхської династій періоду бронзового віку, а також аналізу супутніх міфологічних символів і лексики. Мета роботи полягала в узагальненні теорій щодо існуючих індоєвропейсько-кавказьких мовно-культурних паралелей, а також включенні до компаративістичних досліджень з міфології ритуальних функцій "золотого руна". Паралельне сприйняття солярної і зооморфної культової символіки (барана, бика або їхньої шкури) як знака божественной царської влади, засвідчене в хетських ритуалах і помітне в грецьких і римсько-етруських міфах, походить, імовірно, із західноанатолійского ареалу. Для підтвердження гіпотези балкано-анатолійсько-кавказьких контактів були проведені зіставлення дублетної онімної лексики з коренями: Kaukas-, Ias-, Arg-, Aia-, – на фоні відомих кавказьких запозичень на позначення руна в давньогрецькій мові.
Давньогрецький "міф про аргонавтів" у контексті проблематики балканського етногенезу
Keywords: Indo-European; Caucasian languages and cultures; the Greek ethnogenesis; mythology; cult symbols; sheep and fleece; індоєвропейські; кавказькі мови і культури; грецький етногенез; міфологія; культова символіка; баран і руно